Czekając na przebiśniegi. Rozmowa z Piotrem Słowikowskim - Barczyk, Agnieszka; Słowikowski, Piotr (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The article is a transcription of an interview with Piotr Słowikowski – a journalist from Lodz associated for many years with TVP Lodz (one of the regional branches of TVP, Poland’s public television broadcaster). The conversation focuses on the most significant TV programs (individual and series) produced by Słowikowski, as well as figures he considers to be particularly important for various reasons. Overall, it seems difficult to reconcile the prestigious and educational nature of Słowikowski’s productions with the contemporary perception of television as a medium for sensation and entertainment.